2020
DOI: 10.1021/acsapm.0c00387
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion Behavior of Catechol-Incorporated Silicone Elastomer on Metal Surface

Abstract: Herein, we designed a catechol-based compound, 4allyl pyrocatechol (APC), which contains catechol and alkene groups capable of interacting with various metal oxide substrates and being chemically incorporated into a polydimethylsiloxane (PDMS) matrix, respectively. Due to the specific interactions between the catechol and metal oxide surface, this compound incorporated in PDMS can act as a surface "active" additive that effectively enriches the adhesion interface, leading to the improvement of adhesion between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Their tunable properties and easy moldability make them ideal candidates for stretchable and wearable electronics, 3,4 microfluidics, 4,5 biomaterials, 6–8 cosmetics, 1,9 and soft robotics 1,4,10–15 . Additionally, the ability to tune their mechanical and interfacial properties, combined with their commercial availability in simple, two‐part systems, make silicones useful for fundamental studies on soft materials, including but not limited to adhesion, 9,16–20 friction, 21–23 wetting, 24,25 cavitation, 26 wrinkling, 17,27–29 fracture, 22,26,30 and cell‐surface viability 8,14,31–33 . These elastomers mostly comprise polydimethylsiloxane (PDMS) and, in some cases, additional fillers such as nanoparticles 1,34,35 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their tunable properties and easy moldability make them ideal candidates for stretchable and wearable electronics, 3,4 microfluidics, 4,5 biomaterials, 6–8 cosmetics, 1,9 and soft robotics 1,4,10–15 . Additionally, the ability to tune their mechanical and interfacial properties, combined with their commercial availability in simple, two‐part systems, make silicones useful for fundamental studies on soft materials, including but not limited to adhesion, 9,16–20 friction, 21–23 wetting, 24,25 cavitation, 26 wrinkling, 17,27–29 fracture, 22,26,30 and cell‐surface viability 8,14,31–33 . These elastomers mostly comprise polydimethylsiloxane (PDMS) and, in some cases, additional fillers such as nanoparticles 1,34,35 .…”
Section: Introductionmentioning
confidence: 99%
“…These elastomers mostly comprise polydimethylsiloxane (PDMS) and, in some cases, additional fillers such as nanoparticles 1,34,35 . Commonly, commercial systems use a platinum catalyst to activate a vinyl‐hydride reaction for curing, referred to as hydrosylation 9,36–38 . Additionally, these elastomer systems can be enhanced through the addition of non‐covalent bonds to enhance toughness and dissipate energy 39–41 .…”
Section: Introductionmentioning
confidence: 99%
“…WCA was measured using DI water and diiodomethane with a contact angle measurement system (Phoenix-300, SEO Corporation) equipped with a video capture apparatus. The surface tension of the membrane surfaces was calculated using the Young–Owens–Wendt equation where θ is the contact angle of the testing liquid on the membrane surface, γ α is the surface tension of component α (α = L or S) given as γ α = γ α d + γ α p where γ α d and γ α p are the dispersive and polar contributions of component α, respectively ( 1 + cos θ ) γ normalL = 2 ( γ S d γ L d + γ S p γ L p ) …”
Section: Methodsmentioning
confidence: 99%
“…In the past two decades, the phenomenon by which mussels adhere strongly to the marine environment has aroused great attention. , Systematical studies found that such robust and wide-ranging surface adhesion was mainly due to the presence of a large amount of catechol groups in the mussel foot silk proteins, , which can form one or more interactions, such as hydrogen bonding, coordination interaction, π–π stacking, or covalent bonding with different types of substrate materials. , Inspired by mussels, many catechol-functionalized polymers have been synthesized and widely used in various fields, including adhesives, , energy storage devices, and stimuli-responsive materials. , …”
Section: Introductionmentioning
confidence: 99%
“…18,19 Systematical studies found that such robust and wide-ranging surface adhesion was mainly due to the presence of a large amount of catechol groups in the mussel foot silk proteins, 20,21 which can form one or more interactions, such as hydrogen bonding, coordination interaction, π−π stacking, or covalent bonding with different types of substrate materials. 19,22 Inspired by mussels, many catechol-functionalized polymers have been synthesized and widely used in various fields, including adhesives, 23,24 energy storage devices, 25 and stimuli-responsive materials. 26,27 However, there are only a few studies about catecholfunctionalized conjugated polymers, where catechol groups were usually introduced as the end groups to improve the interaction between conjugated polymers and metal oxide substrates through the coordination of catechol groups with metal atoms.…”
Section: Introductionmentioning
confidence: 99%